Functional and clinical characteristics of focal adhesion kinases in cancer progression - Zhang, Zhaoyu; Li, Jinlong; Jiao, Simin; Han, Guangda; Zhu, Jiaming; Liu, Tianzhou (Frontiers in Cell and Developmental Biology, 2022)
Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase and an adaptor protein that primarily regulates adhesion signaling and cell migration. FAK promotes cell survival in response to stress. Increasing evidence has shown that at the pathological level, FAK is highly expressed in multiple tumors in several systems (including lung, liver, gastric, and colorectal cancers) and correlates with tumor aggressiveness and patient prognosis. At the molecular level, FAK promotes tumor progression mainly by altering survival signals, invasive capacity, epithelial-mesenchymal transition, the tumor microenvironment, the Warburg effect, and stemness of tumor cells. Many effective drugs have been developed based on the comprehensive role of FAK in tumor cells. In addition, its potential as a tumor marker cannot be ignored. Here, we discuss the pathological and pre-clinical evidence of the role of FAK in cancer development; we hope that these findings will assist in FAK-based clinical studies.